First direct evidence of involvement of a homozygous loss‐of‐function variant in the EPS15L1 gene underlying split‐hand/split‐foot malformation. Issue 3 (25th January 2018) - Umair, M.; Ullah, A.; Abbas, S.; Ahmad, F.; Basit, S.; Ahmad, W.
Abstract : Split‐hand/split‐foot malformation (SHFM) is a severe form of congenital limb deformity characterized by the absence of 1 or more digits and/or variable degree of median clefts of hands and feet. The present study describes an investigation of a consanguineous family of Pakistani origin segregating SHFM in an autosomal recessive manner. Human genome scan using SNP markers followed by whole exome sequencing revealed a frameshift deletion (c.409delA, p.Ser137Alafs*19) in the EPS15L1 gene located on chromosome 19p13.11. This is the first biallelic variant identified in the EPS15L1 gene underlying SHFM. Our findings report the first direct involvement of EPS15L1 gene in the development of human limbs. Abstract :